Water Transfer by The Toad Bladder - Sulaiman Ibrahim (Agricultural Faculty, 2000)
ABSTRACT.Studies have been made on the isolated urinary bladder of the toad, Bufo marinus, in an attempt to investigate the effect of vasopressin on the permeability of water from mucosal surface to serosal surface of the toad bladder. The method adapted was that described by Bentley ( 1 ). The bilobed bladder of the toad is devided into two separate sacs. Each of the sacs is filled with a dilute Ringers solution and then immersed in aerated isotonic Ringers solution. The rate of water loss along the imposed osmotic gradient is estimated by weighing the sacs in air at 30 minute intervals and nothing the weight loss in that time period. In most studies one bladder sac serves as a control for the contra lateral experimental obtained from the same animal. Osmotic flow of water is negligible in both sacs during the initial control periods. However, the addition of vasopressin to the solution bathing the serosal surface of the membrane result in a market increase in net water movement. The effect is readily reversed by rinsing the bladder and adding hormone free Ringgers solution to the serosal surface. Characteristically no response is elicited by addition of hormone to the mucosal bathing solution.